A physician with a soul of a cook? Entrepreneurial personality across occupations - Alina Sorgner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
There is a debate in the literature backed by ambiguous empirical evidence whether personality is useful at predicting entrepreneurship behavior. However, little is known about the role of the context in the relationship between personality and entrepreneurship. This paper draws on the well-established psychological theory of vocational behavior, which emphasizes the crucial role of personality for peoples' vocational choices, in order to shed more light on the interplay between personality, occupational environment, and the decision to become self-employed. Empirical findings suggest that personality is associated with both vocational and entrepreneurial choices. An entrepreneurial personality profile is positively related to the choice of Holland's enterprising and artistic occupations, which contributes to above-average self-employment rates in these occupations. Personality also seems to play an important role in entrepreneurial choice, however, in a way which varies substantially across occupations.
Keywords: L26; J24; J44; 330; entrepreneurship; vocational choice; Big Five; occupational environment; Unternehmer; Selbstständige; Berufswahl; Persönlichkeitspsychologie